Basing motoblock the main parametres of the potato digger - Masharibov Anvarbek; Xusainov Baxtiyor; Ismoilov Raxmatjon; Eshankulov Ulash; Do‘schonov Shodyorbek (BIO Web of Conferences)
This article will consider the main parameters of a potato digger designed to work with tillers in order to increase the efficiency of mechanized potato harvesting in small and medium-sized farms. The study highlights the importance of optimizing the design and operational characteristics of the potato digger, such as digging depth, oscillation amplitude, sieving efficiency, and energy consumption. The study uses a combination of theoretical modeling and field experiments to evaluate the effectiveness of potato digging in various soil conditions and in the cultivation of various crops. The results show that proper adjustment of the digging mechanism and vibration frequency can significantly reduce soil resistance, increase work speed, and reduce damage to tubers during harvest. In addition, the results show the economic and environmental benefits of using potato diggers compatible with tillers, including reduced labor intensity and resource consumption. This research will help to develop innovative environmentally friendly solutions for small farms, meeting the demand for cost-effective mechanization in modern agriculture and ensuring high quality and productivity.